ANALYSIS OF FOOD SECURITY FACTORS WITH PATH MODELING SEGMENTATION TREE (PATHMOX) METHOD IN PARTIAL LEAST SQUARES IN WEST KALIMANTAN - Harnanta, Nabila Izza; Perdana, Hendra; Satyahadewi, Neva (PATTIMURA UNIVERSITY, 2025)
Food security is essential for ensuring community well-being by guaranteeing sufficient, safe, and nutritious food, particularly in regions with complex socio-economic conditions. This study analyzes food security in West Kalimantan Province by identifying key influencing factors, constructing a structural equation model, and segmenting regions based on their food security characteristics. Utilizing secondary data from the 2023 Food Security and Vulnerability Atlas (FSVA), the research employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the Path Modeling Segmentation Tree (PATHMOX) approach. The study incorporates ten indicators across four latent variables: food availability, food access, food absorption, and overall food security. The results reveal that regional segmentation using the PATHMOX approach effectively identifies data heterogeneity, categorizing West Kalimantan’s 14 districts/cities into two distinct groups based on the Human Development Index (HDI). The first group (10 regions) exhibits higher food consumption despite socio-economic challenges, whereas the second group (4 areas) demonstrates better food security yet lower intake levels. These findings highlight that food security is influenced by access, distribution, and policy implementation rather than solely by the Normative Consumption Production Ratio (NCPR). The insights from this study provide a foundation for developing targeted policies to enhance food security strategies in West Kalimantan Province, ensuring a more sustainable and equitable food system. By applying PATHMOX segmentation, policymakers can address regional disparities more effectively, fostering strategic interventions that improve food availability, accessibility, and utilization across different population groups.